Evaluation of the activities of the medial and lateral heads of quadratus plantae in flexion movements of the lateral four toes using ultrasound real-time tissue elastography. (September 2018) - Nakanowatari, Tatsuya; Koseki, Tadaki; Sato, Takuya; Kanzaki, Hideto; Kiyoshige, Yoshiro
Highlights: What is already known Quadratus plantae assists flexor digitorum longus in flexion of the lateral four toes and contributes to postural control. A relationship between the evolutionary appearance of the medial head of quadratus plantae in humans and the demands of bipedalism has been suggested. Ultrasound real-time elastography can assess the activities of regional deep-layer muscles. What this study adds In the medial head of quadratus plantae, muscle hardness assessed by the strain ratio increased during second toe flexion movement. In the lateral head of quadratus plantae, muscle hardness assessed by the strain ratio increased during second to fifth toe flexion movement. Using ultrasound real-time elastography could differentiate the functions of the two heads of quadratus plantae. Abstract: Quadratus plantae (QP), one of the plantar intrinsic foot muscles, assist plantarflexion of the lesser toes. QP has medial and lateral muscle heads with different anatomical structures. The two heads of this muscle may have different roles in foot function. Ultrasound real-time tissue elastography (RTE) measurements have allowed quantitative assessment of deep-layer muscle elasticity. The purpose of this study was to determine the activity of the QP in flexion movements of the lateral four toes using RTE. Thirteen healthy subjects performed maximal voluntary contractions using a hand-held dynamometer with external belt fixation for each toe flexion movement. The elasticity of the muscles were measured using RTE during rest and flexion of each toe. The strain ratio of the muscle to that in an acoustic coupler was calculated as an index of muscle elasticity. Higher strain ratio values imply lower elasticity. The strain ratio of the medial head of QP for second toe flexion (0.10 ± 0.11) was significantly stiffer than at rest (0.34 ± 0.33). The strain ratios of the lateral head of QP for flexion of the second (0.32 ± 0.19), third (0.41 ± 0.37), fourth (0.33 ± 0.26), and fifth (0.45 ± 0.39) toes were significantly stiffer than at rest (1.02 ± 0.68). These results suggest that the medial head of QP has a role in assisting second-toe flexion, and the lateral head has a role in assisting flexion of all four lateral toes.